569. Utility of the Meningoencephalitis Panel in Modifying Antimicrobial Use in Neonates with Temperature Instability. (15th December 2022) - Player, Brittany; Havens, Peter; Mitchell, Michelle L; Bushee, Glenn; Pan, Amy; Huppler, Anna R
Abstract: Background: Decisions to discontinue antibiotics in infants undergoing evaluation for central nervous system (CNS) infection can be difficult. Previous reports have associated the use of the meningoencephalitis (ME) PCR panel with decreased hospital stay and antimicrobial use in pediatric and adult patients. However, limited focus has been on infants ≤60-days-old with temperature instability (TI) who undergo evaluation for serious bacterial infection based on age and risk-stratification. We hypothesize use of the ME panel will decrease the duration of antimicrobial use in infants with TI and negative bacterial cultures undergoing evaluation for CNS infection. Methods: The electronic medical record was queried for patients that met inclusion criteria. Infants ≤60-days-old evaluated for CNS infection due to TI between 1/1/12 – 1/31/22 were included. Exclusion criteria were history of intracranial (IC) devices, previous IC surgery, IC structural or neurovascular abnormalities, or head trauma. A retrospective chart review was performed. We compared length of stay and antimicrobial duration for the groups of patients with the ME panel done versus not done. Results: A total of 1808 patients with negative bacterial cultures were identified, 96 of whom had the ME panel performed. Patient age, sex, and race were similar between groups. The median hospital length of stay for the patients that had the ME panel done was 64.7 hours as compared to 47.8 hours for those that did not have the ME panel done. The duration of antibacterial therapy was similar when the ME panel was done versus not done. The median duration of therapy for acyclovir was 8.5 when the ME panel was done versus 14.8 hours when it was not done. Conclusion: When including all patients ≤60-days-old evaluated for TI, use of the ME panel did not lead to a shorter length of hospital stay or duration of empiric antibiotics. However, use of the ME panel decreased duration of therapy in the subset of patients empirically started on acyclovir. Further data analysis will seek to identify patient populations that may most benefit from the use of the ME panel. Disclosures: All Authors : No reported disclosures.